Market Access and Development of the ICT Sector in the West Bank - Fratto, Chiara; Giannone, Elisa (World Bank, Washington, DC, 2020)
Despite the popular view that, with the advent of digital technologies, the world has become flat, geography still plays a key role in the economy. COVID-19 has brought even more awareness of this. This paper studies the impact of security measures that have reduced the mobility of people and goods on the industrial composition of the West Bank economy, and, in particular, on the development of the information and communications technology sector. The paper identifies different channels through which changes in market access due to the introduction of mobility restrictions can differentially affect industries. A newly designed survey instrument is used to identify and disentangle these mechanisms separately. This novel data set contains information on more than 500 establishments that are representative of different sectors of the economy, including information and communications technology, manufacturing, and retail trade. The analysis finds that the mobility restrictions involved a reallocation of resources toward the information and communications technology sector, as the industry was relatively less affected by the restrictions. Yet, the key role of the input-output linkages, strong dependence on local clients and suppliers, and deep interconnectedness of the information and communications technology sector with other domestic industries severely limit the extent to which the sector can benefit from the reduction in opportunity cost. An industrial strategy focusing on the harmonious development of the entire economy is advised, rather than targeting a specific industry in isolation from the rest.